Treatment and prevention of acute respiratory infections among Iranian hajj pilgrims: a 5-year follow up study and review of the literature - Razavi, Seyed Mansour (Iran University of Medical Sciences, 2014)
Background Respiratory diseases/syndromes are the most common causes of referring to physicians among pilgrims in Hajj. They lead to high morbidity, impose high costs on the health system and are among the major obstacles for pilgrims to perform Hajj duties. The main aim of our study was to determine types, frequencies, etiologies, and epidemiologic factors of respiratory diseases among Iranian Hajj pilgrims and to suggest some preventive and treatment strategies. Methods: To determine the types and frequencies of respiratory syndromes, we implemented a syndromic surveillance method in Iranian health care system for Hajj during 5 consecutive years. To achieve the etiology of these diseases, we performed 4 concurrent before and after studies. We also evaluated efficacy of the flu and pneumovax vaccines among Iranian Hajj pilgrims in 2 studies. To determine some other epidemiological factors, we conducted 4 additional studies. Results: The most common problem was common cold like syndrome. Origins of the most upper respiratory problems were infections, and allergies were less involved. Among infectious agents, viruses were the most common agents and their frequencies were as follows respectively: Adenoviruses 38 (36.2 %), Rhinoviruses 31 (30%), Influenza type B virus 21 (20%). Bacteria were often the secondary causes and their frequencies were as follows respectively: Intestine bacillus 69 (19.4%), Chlamydia pneumonia 20(15.8%), Haemophiluses 32 (9.1%) and Streptococcus (A,C and G) 30 ( 8.5%). We introduced some epidemiological factors as effective in creating respiratory diseases. Conclusion: In this paper, we suggested some applied points for prevention, treatment, and correction of common malpractices in the treatment of respiratory diseases of the pilgrims.